ANALISIS KEBUTUHAN DAN KETERSEDIAAN TELUR AYAM DALAM IMPLEMENTASI PROGRAM MAKAN BERGIZI DI KECAMATAN BOAWAE KABUPATEN NAGEKEO: ANALISIS KEBUTUHAN DAN KETERSEDIAAN TELUR AYAM DALAM IMPLEMENTASI PROGRAM MAKAN BERGIZI DI KECAMATAN BOAWAE KABUPATEN NAGEKEO - Nago Azi, Maria Dominika; Freadyanus Kasi, Yohanes; Andhi Prastiwi, Marcellena (Fakultas Pertanian dan Peternakan Universitas Muhammadiyah Bengkulu, 2025)
This study aims to determine the availability of chicken eggs to support the implementation of the free nutritious meal program in Boawae District, Nagekeo Regency. It also analyzes the factors influencing the gap between the availability and demand for chicken eggs in the free nutritious meal program. It also analyzes the quantity of chicken eggs available in Boawae District to facilitate the implementation of the free nutritious meal program. It also predicts the availability of chicken eggs in Boawae District. The research method used a quantitative descriptive approach with a purposive sampling technique. Data were obtained through documentation, field observations, and interviews with relevant agencies, farmers, and the local community. The results indicate that the local availability of chicken eggs is insufficient to fully meet the program's needs. Keywords: Need, Availability, Chicken Eggs